Standardization of protocol for in vitro multiplication of bougainvillea - JAIN, RITU; JANAKIRAM, T; SWAROOP, KISHAN; KUMAR, SURENDRA; KUMAWAT, G L (The Indian Journal of Agricultural Sciences, 2016)
Bougainvillea is commonly propagated by hardwood cuttings but this method is tedious and time consuming. Moreover, there are certain varieties where the rooting percentage is very low. For easy, quick and mass multiplication of such cultivars, tissue culture technique can be put to use. Tissue culture has been proved to be useful for successful multiplication in case of number of vegetatively propagated shrubs. Present investigation was carried out in order to standardize a protocol for in vitro multiplication of bougainvillea cultivar Mahara through axillary bud induction of nodal explants. Shoot tips and nodal sections with axillary buds were excised, surface-sterilized and then cultured on MS medium supplemented with plant growth regulators. Pre-treatment agitation of explants in Carbendazim (0.2%) + Diathane M-45 (0.2%) + 8-HQC (200 mg/l) for 2 hr followed by quick dip in ethyl alcohol (70%; v/v) for 30 sec and surface sterilization with HgCl2 (0.1%) for 5 min was found to be most effective in culture initiation with only 16.48% microbial contamination. For culture establishment, MS medium supplemented with BAP (5mg/L)+ NAA (0.5mg/l) was found to be the best with highest percentage of culture establishment (100%) and the fastest bud sprout (4.50 days). MS medium supplemented with BAP (5.0 mg/l)+ NAA (1.0mg/l) and GA3 (0.5 mg/l) gave the highest shoot proliferation. The best treatment for micro-shoot elongation was MS medium was supplemented with 1.5 mg/l GA3 which gave the highest elongation (2.34 cm). Highest in vitro rooting (70.52%) of micro-shoots was observed in the treatment where, half-strength MS medium was supplemented with IBA (1.0 mg/l)+ NAA (1.0 mg/l). Hardening of in vitro propagated plants of bougainvillea rooted plantlets was done for 21 days in glass jars filled with agro peat medium A mixture of soilrite (1) + coco peat (1) + perlite (1) supplemented with 1/2 strength liquid inorganic MS medium and covered with polypropylene lids. The hardened plantlets were successfully transferred to the glasshouse after a short period of in vitro acclimatization.